2022
DOI: 10.31788/rjc.2022.1525294
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF SECONDARY METABOLITE COMPOUNDS FROM Elaeocarpus mastersii KING STEM BARK AND THEIR BIOLOGICAL ACTIVITY EVALUATION

Abstract: In this research, isolation of secondary metabolites of Elaeocarpus mastersii King stem bark was conducted by column chromatography and pure compounds were characterized by the IR, UV, and NMR spectra. The biological activity of the isolated compounds as antidiabetic was determined based on the α-glucosidase inhibition. The investigation led to isolate β-sitosterol (1), β-sitosterol glucoside (2), and cucurbitacin F(3). The evaluation of the αglucosidase inhibitory assay showed that the isolated compounds had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Berdasarkan hasil pengukuran spektrum UV-Vis menunjukkan bahwa pita serapan maksimum (λ max ) pada panjang gelombang 224,80 nm. Pada panjang gelombang ini terjadi transisi elektron n-π* yang menunjukkan terbentuknya kromofor dari ikatan rangkap (C=O) 13 . Hal ini menunjukkan bahwa dari senyawa hasil isolasi tidak ada ikatan rangkap berkonjugasi.…”
Section: Uji Kemurnian Senyawa Dari Fraksi Heksana Tumbuhan Sirih Mer...unclassified
See 1 more Smart Citation
“…Berdasarkan hasil pengukuran spektrum UV-Vis menunjukkan bahwa pita serapan maksimum (λ max ) pada panjang gelombang 224,80 nm. Pada panjang gelombang ini terjadi transisi elektron n-π* yang menunjukkan terbentuknya kromofor dari ikatan rangkap (C=O) 13 . Hal ini menunjukkan bahwa dari senyawa hasil isolasi tidak ada ikatan rangkap berkonjugasi.…”
Section: Uji Kemurnian Senyawa Dari Fraksi Heksana Tumbuhan Sirih Mer...unclassified
“…Pada bilangan gelombang 1456,26 tekuk CH 2 dan 1367,53 cm -1 menunjukkan adanya gugus geminal dimetil yang merupakan ciri khas dari senyawa triterpenoid. Kemudian pada bilangan ge-lombang 1240,23, 1192,01 cm -1 dan 1051,20 cm -1 menunjukkan adanya gugus C-O (alkohol) 13,15,16 . Perbedaan kekuatan aktivitas antibakteri disebabkan karena adanya perbedaan kandungan metabolit sekunder.…”
Section: Gambar 4 Spektrum Uv Senyawa Hasil Isolasiunclassified
“…This plant has high total phenolic contents [16,17]. Unfortunately, the literature studies showed that the isolated compounds of E. mastersii King were limited to the compounds of anthocyanins, cucurbitacins, ellagic acid derivatives, β-sitosterol, and βsitosterol glucoside [18][19][20]. Therefore, the aim of this study was to isolate the phenolic compounds of E. mastersii King leaves.…”
Section: Introductionmentioning
confidence: 99%